PG7 Mountain Rescue Simulation. (10th November 2020) - Mason, Timothy; Bartle, David; Thompson, Ross; Schwinge, Rene; Morris, Ben
Abstract : Background: As part of the Royal Devon and Exeter Hospital Primary care simulation project, we performed a simulation session with North Dartmoor search and Rescue rescue team (part of Mountain rescue England and Wales). This is a volunteer emergency service comprised of people who may or may not be medically trained. Training involves weekly drills but they had never undertaken an in-situ simulation. It was commented by a member of the group (pre-simulation) that usual training was didactic and questioned whether a simulation approach would be welcomed. In situ simulation training has been proven to improve patient outcomes 1. Formal simulation training with mountain rescue teams has not been widely documented but when surveyed a Mountain Helicopter Emergency Medical Services team in Europe found that it led to increased subjective self-assuredness in the context of human factors and team resource management 2. Summary of Educational Project: A Simulated casualty (actor) was taken to a location of the edge of Dartmoor away from base (evening January 2020) where a simulated distress call was made. We assigned faculty to each group/area to observe closely. The call was for a man who's gas stove exploded whilst he was wild camping, he fell backwards sustaining an open fracture of his ankle and airway burns. The distress call was located teams were formed and was dispatched from base. He was treated and extracted to the main road. There were multiple challenges for the team as it was dark, cold, in a small wood, and next to a loud river. Summary of Results: 20 learners took part with 11 giving formal feedback. 100% Agreed or strongly agreed that this session was useful, was relevant and increased their confidence. Written feedback was overwhelmingly positive and included that the scenario had a 'realistic casualty, and that there was 'blame free feedback'. Learning included medical, technical and non-technical areas. Challenges for the simulation team were, safety (dark, cold and wet), observing multiple teams, debriefing to a large group who had never experienced simulation before. These were counteracted through planning, having a thorough brief, appropriate number of faculty and hot chocolate. Conclusions/Recommendations: Simulation with a volunteer mountain rescue team was welcomed as a realistic, relevant and useful form of training ( despite being very different from usual training). Survey post session suggested subjective increased confidence in managing a similar scenario. Reference: Pietsch, Urs & Knapp, Jürgen & Ney, Ludwig & Berner, Armin & Lischke, Volker. Simulation-based training in mountain helicopter emergency medical service: a multidisciplinary team training concept. Air Medical Journal 2016;35:10.1016/j.amj.2016.05.006. Goldshtein D, Krensky C, Doshi S, et al. In situ simulation and its effects on patient outcomes: a systematic review. BMJ Simulation and Technology Enhanced Learning 2020;6:3–9.